RELIABILITY ANALYZES OF THE ARMENIAN “BIG FIVE” QUESTIONNAIRE - Serobyan, A. K. (Modern Psychology, 2018)
Questionnaires studying the Big Five have been translated into many languages (for example, in Russian, German, French, etc.). Their adapted versions are actively used during the studies in the field of personality psychology. There is practically no such adapted methods in Armenian. So there was a need for creating the Armenian “Big Five” questionnaire. The article presents the reliability analyzes (Cronbach’s alpha) and the stability analyzes (test-retest correlation coefficients) of the Armenian “Big Five” questionnaire. The results show that the Cronbach’s alpha and test-retest coefficient for all the five scales has been obtained high enough that the questionnaire will be considered reliable.